Fire safety and emergency evacuation guidelines for intensive care units and operating theatres: for use in the event of fire, flood, power cut, oxygen supply failure, noxious gas, structural collapse or other critical incidents: Guidelines from the Association of Anaesthetists and the Intensive Care Society. (13th May 2021) - Kelly, F. E.; Bailey, C. R.; Aldridge, P.; Brennan, P. A.; Hardy, R. P.; Henrys, P.; Hussain, A.; Jenkins, M.; Lang, A.; McGuire, N.; McNarry, A.; Osborn, M.; et al.
Summary: The need to evacuate an ICU or operating theatre complex during a fire or other emergency is a rare event but one potentially fraught with difficulty: Not only is there a risk that patients may come to harm but also that staff may be injured and unable to work. Designing newly‐built or refurbished ICUs and operating theatre suites is an opportunity to incorporate mandatory fire safety features and improve the management and outcomes of such emergencies: These include well‐marked manual fire call points and oxygen shut off valves (area valve service units); the ability to isolate individual zones; multiple clear exit routes; small bays or side rooms; preference for ground floor ICU location and interconnecting routes with operating theatres; separate clinical and non‐clinical areas. ICUs and operating theatre suites should have a bespoke emergency evacuation plan and route map that is readily available. Staff should receive practical fire and evacuation training in their clinical area of work on induction and annually as part of mandatory training, including 'walk‐through practice' or simulation training and location of manual fire call points and fire extinguishers, evacuation routes and location and operation of area valve service units. The staff member in charge of each shift should be able to select and operate fire extinguishers and lead an evacuation. Following an emergency evacuation, a network‐wide response should be activated, including retrieval and transport of patients to other ICUs if needed. A full investigation should take place and ongoing support and follow‐up of staff provided.